Biomechanical Analysis of Stem Malalignment in Resurfacing Hip Arthroplasty - Hisyam Marwan, Shahrul; Aiman Nor Izmin, Nor; Berhan, Muhaimin; Halim Abdullah, Abdul (International Journal of Engineering and Technology, 2018)
Hip resurfacing arthroplasty was developed as an alternative surgical procedure to total hip arthroplasty. In this procedure, the femoral head is not removed; instead it is cut or trimmed and then capped with a metal cap. This procedure is not new news in surgery; it has been performed since the early 1970â€™s. Basically, there are common complications between these two procedures which are fracture, malalignment of implant, bleeding and dislocation. Thus, in this study, the malalignment of implant was found to often occur in different conditions such as varus, valgus, anterversion and retroversion conditions. The objective of this study was to develop the finite element models of Hip Resurfacing Arthroplasty, to investigate the biomechanical behavior of hip arthroplasty and to examine the effects of implant malalignment as to predict the stability of the femoral component. The analyses were done under the loading conditions during normal walking for five cases of implant malalignment which were varus, valgus, sagittal extended and sagittal flexed. Both the femur and implant were developed and analyzed using computational software, namely ABAQUS 6.13. This study demonstrates that resurfacing arthroplasty will have harmful biomechanical effects when the implants are misaligned during the procedure.Â Â Â